Ideology or reality? The awareness of educational aims and activities amongst German and Norwegian participants of the first summer and winter Youth Olympic Games - Krieger, J.; Kristiansen, E. (Sport in Society: Cultures, Commerce, Media, Politics, 2016)
This paper explores the awareness of the young German and Norwegian participants in the Youth Olympic Games (YOG) of the additional educational mission of this new event, implemented by the International Olympic Committee. Among the questions considered are whether the nature of the event contradicts its claimed intention to focus on both competition and education. Data were collected through a set of interviews with young German and Norwegian athletes at the Singapore YOG in the summer of 2010 and the Innsbruck YOG in the winter of 2012. The findings revealed (1) a focus on elite sport by athletes and their coaches, while the educational aims were considered secondary; (2) that it was problematic for the young participants to focus on education in a high-performance event. The overall conclusion was that the YOG have had only limited success in achieving the educational ambitions of the Olympic Movement.